Model Development for Measuring and Analyzing Green Accounting Activities Using Factor Analysis - Lisa Kartikasari; Dian Essa Nugrahini (Universitas Islam Sultan Agung, Faculty of Economic and Business, Accounting Dept, 2025)
One of Corporate social responsibilities to the environment is by disclosing environmental information as a result of industrial activities or their business. It covers a clear figure of a company to combine cost and environmental benefits in economic decision making reflected in the implementation of green accounting. The purpose of this study is to establish indicators and constructs of green accounting activities by identifying environmental activities grouped into the green support, appraisal, internal failure activities, external failure activities and hidden activities. The population in this research is manufacturing companies in the Central Java province which is administered by purposive sampling technique. It is obtained a sample of 43 companies. Then, the data are analyzed by using factor analysis in order to establish and construct appropriate indicators for green accounting.The findings show that 21 selected indicators with five constructs of green accounting activities. Five constructs with the respective variables as follows: green support activities with six indicators, green appraisal activities with four indicators, green internal failure activities with five indicators, green external failure activities with three indicators and green hidden constructs activities with three indicators. ABSTRAKSalah satu tanggung jawab sosial Perusahaan terhadap lingkungan hidup adalah dengan mengungkapkan informasi lingkungan hidup sebagai akibat dari kegiatan industri atau usaha. Hal ini mencakup gambaran jelas suatu perusahaan dalam menggabungkan biaya dan manfaat lingkungan dalam pengambilan keputusan ekonomi yang tercermin dalam penerapan green accounting. Tujuan dari penelitian ini adalah untuk menetapkan indikator dan konstruksi aktivitas green accounting dengan mengidentifikasi aktivitas lingkungan yang dikelompokkan menjadi aktivitas green support, appraisal, internal failure activities, external failure activities dan hidden activities. Populasi dalam penelitian ini adalah perusahaan manufaktur di provinsi Jawa Tengah yang diambil dengan teknik purposive sampling. Diperoleh sampel sebanyak 43 perusahaan. Kemudian, data tersebut dianalisis dengan menggunakan analisis faktor untuk menetapkan dan menyusun indikator-indikator yang sesuai untuk green accounting. Temuan menunjukkan bahwa 21 indikator terpilih dengan lima konstruk kegiatan green accounting. Lima konstruk dengan masing-masing variabel sebagai berikut: aktivitas green support dengan enam indikator, aktivitas green appraisal dengan empat indikator, internal failure activities dengan lima indikator, external failure dengan tiga indikator, dan hidden activities dengan tiga indikator.